MEAN IOP CHANGE IN NON-GLAUCOMATOUS PATIENTS WITH MACULAR EDEMA SUBSEQUENTLY INTRAVITREAL INJECTION AVASTIN - Anwar, Adila; Awan, Ayyaz Hussain; Imdad, Anjum; Khan, Sufian Ali; Shah, Mutahir; Naeem, Misbah (Journal of Ayub Medical College Abbottabad, 2023)
Background: The accumulation of fluid between the retinal layers is called retinal or macular oedema, while intraretinal oedema, or macular oedema, and refers to fluid accumulation directly within the retinal. Purpose of the study was to evaluate the effects of intravitreal injections of bevacizumab on intraocular pressure (IOP) in Non-Glaucomatous patients with Macular Oedema. Methods: A pre-and post-interventional study was conducted. 220 patients were studied utilizing a non-probability, consecutive sampling method. Open Epi software was used to determine the sample size. The department of ophthalmology at Islamabad's Tertiary Care Hospital hosted the study, which lasted six months. Results: The study's participants ranged in age from 30 to 60, with a mean age of 50.38±6.53 years. Male to female ratio of these 220 patients was 1:1.6, with 86 (39.09%) men and 134 (60.91%) women. The mean IOP at baseline was 11.57±1.42 mmHg, and the mean IOP one month after the injection was 12.81±1.18 mmHg, with a mean change in IOP of 1.24±0.87 mmHg. Conclusion: This study found that non-glaucomatous patients with macular oedema experienced a high mean change in intraocular pressure (IOP) after intravitreal Avastin.